RPE-Derived Work Rates Can Be Accurately Produced without External Feedback or Reference to the RPE Scale. Issue 2 (April 2014) - Mauger, Alexis R.; Huntley, Tabo; Fletcher, Iain M.
Ratings of perceived exertion (RPE) are used to prescribe exercise intensity. This study assessed whether the accurate production of exercise intensity is affected when the rater cannot see the RPE scale. After completing a graded exercise test, 15 active, male participants ( M age = 34, SD = 6.7 yr.; M mass = 73.9, SD = 14.8 kg, M height = 1.74, SD = 0.08 m) completed 3 × 4 min. cycling trials at four randomised RPE-based intensities (RPEs 11, 13, 15, and 17). Participants were allocated to a Full feedback group or a No feedback group (RPEs not in view). On the third trial, No feedback conditions were imposed on the Full feedback group. No statistically significant differences between groups' mean work rates were observed. Changing from Full feedback to No feedback conditions led to a significant overestimation between the trials for power output at RPE 11. Intra-class correlations were significant at RPEs 11, 13, and 17 between all trials for both conditions. Provided adequate familiarisation, active participants can accurately produce RPE derived work rates, even when RPE is not in view.